Thermochromic properties of vanadium oxide films prepared by dc reactive magnetron sputtering - Cui, Hai-Ning (2008)
A transparent vanadium oxide film has been one of the most studied electrochromic (EC) and Thermochromic (TC) materials. Vanadium oxide films were deposited at different substrate temperatures up to 400 °Cand different ratios of the oxygen partial pressure (PO2). SEM,AFMand X-ray diffraction's results show detail structure data of the films. IR mode assignments of the films measured by IR reflection–absorbance in NGIA (near grazing incidence angle) are given. It is found that the film has V2O5 and VO2 combined structures. The films exhibit clear changes in transmittance when the environment temperature (Te) is varied, especially in the 3600–4000 cm−1 range. Applying a Te that is higher than a critical temperature (Tc) to the samples, the as-RT (room temperature) deposited film with 9% PO2 has a transmittance variation of 30%, but the films that were deposited on a heated substrate of 400 °C have little variation. There is tendency of bigger variation in transmittance for the sample deposited at a larger PO2, when it is applied by 200 °C Te.